Identification of Paracentrone in Fucoxanthin‐Fed Mice and Anti‐Inflammatory Effect against Lipopolysaccharide‐Stimulated Macrophages and Adipocytes. Issue 2 (7th December 2020) - Takatani, Naoki; Taya, Daisuke; Katsuki, Ami; Beppu, Fumiaki; Yamano, Yumiko; Wada, Akimori; Miyashita, Kazuo; Hosokawa, Masashi
Abstract : Scope: Fucoxanthin is converted to fucoxanthinol and amarouciaxanthin A in the mouse body. However, further metabolism such as cleavage products (i.e., apocarotenoids) remains unclear. The fucoxanthin‐derived apocarotenoid in vivo is investigated and the anti‐inflammatory effect of apocarotenoids with fucoxanthin partial structure such as allenic bond and epoxide residue against activated macrophages and adipocytes in vitro is evaluated. Methods and Results: LC‐MS analysis indicates the presence of paracentrone, a C31 ‐allenic‐apocarotenoid, in white adipose tissue of diabetic/obese KK‐ A y and normal C57BL/6J mice fed 0.2% fucoxanthin diet for 1 week. In lipopolysaccharide‐activated RAW264.7 macrophages, paracentrone as well as C26 ‐ and C28 ‐allenic‐apocarotenoids suppresses the overexpression of inflammatory factors. Further, apo‐10′‐fucoxanthinal, a fucoxanthin‐derived apocarotenoid which retained epoxide residue, exhibits a most potent anti‐inflammatory activity through regulating mitogen‐activated protein kinases and nuclear factor‐ κ B inflammatory signal pathways. In contrast, β‐apo‐8′‐carotenal without allenic bond and epoxide residue lacks suppressed inflammation. In 3T3‐L1 adipocytes, paracentrone, and apo‐10′‐fucoxanthinal downregulate the mRNA expression of proinflammatory mediators and chemokines induced by co‐culture with RAW264.7 cells. Conclusion: Dietary fucoxanthin accumulates as paracentrone as well as fucoxanthinol and amarouciaxanthin A in the mouse body. Allenic bond and epoxide residue of fucoxanthin‐derived apocarotenoids have pivotal roles for anti‐inflammatory action against activated macrophages and adipocytes. Abstract : Fucoxanthin is converted to fucoxanthinol and amarouciaxanthin A in the mouse body. However, further metabolism such as cleavage products (i.e. apocarotenoids) and biological activity of fucoxanthin‐derived apocarotenoid remains unclear. In this study, paracentrone is identified in vivo. Furthermore, other synthesized apocarotenoid (e.g., apo‐10′‐fucoxanthinal) including paracentrone exerts anti‐inflammatory action against lipopolysaccharide‐stimulated macrophages and an obesity‐related adipose tissue in vitro model (coculture system).